2021
DOI: 10.1002/tcr.202100227
|View full text |Cite
|
Sign up to set email alerts
|

Site and Enantioselective Aliphatic C−H Oxidation with Bioinspired Chiral Complexes

Abstract: Selective oxidation of aliphatic C−H bonds stands as an unsolved problem in organic synthesis, with the potential to offer novel paths for preparing molecules of biological interest. The quest for reagents that can perform this class of reactions finds oxygenases and their mechanisms of action as inspiration motifs. Among the numerous families of synthetic catalysts that have been explored, complexes with linear tetraazadentate ligands combining two aliphatic amines and two aromatic amine heterocycles display … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 130 publications
0
19
0
Order By: Relevance
“…Though, it is clear now that even relatively subtle electronic effects (alongside with steric effects) should not be discounted when designing novel non‐heme Fe based catalysts for direct oxidation of C−H groups, which glorifies rational ligand‐oriented catalyst design as a potentially highly rewarding investment of efforts. We share the expectation that hon‐heme Fe based catalyst systems are to expand their synthetic utility, [3i] and hope that this account will be of interest for catalytic chemists interested in developing synthetic approaches to late‐stage oxidative functionalization of complex substrates, from both fundamental and practical perspectives.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Though, it is clear now that even relatively subtle electronic effects (alongside with steric effects) should not be discounted when designing novel non‐heme Fe based catalysts for direct oxidation of C−H groups, which glorifies rational ligand‐oriented catalyst design as a potentially highly rewarding investment of efforts. We share the expectation that hon‐heme Fe based catalyst systems are to expand their synthetic utility, [3i] and hope that this account will be of interest for catalytic chemists interested in developing synthetic approaches to late‐stage oxidative functionalization of complex substrates, from both fundamental and practical perspectives.…”
Section: Discussionmentioning
confidence: 90%
“…This issue needs further investigations. Nevertheless, the consensus mechanisms of Fe(PDP) catalyzed epoxidations (proceeding through rate‐limiting electron transfer, with formation of acyclic, presumably electron‐deficient intermediate) [13c] and C−H oxidations (occurring essentially via oxygen rebound mechanism) [3i,5f] includes the common formally perferryl species (Scheme 1).…”
Section: Discovery Of the First Oxoiron(v) Intermediatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Disclosing the mechanistic landscape of these versatile oxidative transformations is of particular interest. Based on the previous background, 11,20,21,38 we believe that the first step, intramolecular C−H bond cleavage, is conducted by the presumably Mn V �O complex (Scheme 1). In this case, the fatty acid serves as both the cocatalytic additive, facilitating the O−O bond heterolysis, 24,36 and as the substrate at the same time.…”
Section: T H Imentioning
confidence: 96%
“…It contains the highly sterically demanding benzhydryl substituents as well as strongly electron-donating methoxy substituents at the pyridine moieties of the ligand. X-ray characterization (SI) revealed that 7 featured the same cis -α topology as other catalytically active complexes of the PDP family. ,,, Complex 7 and a series of other (previously reported) manganese complexes 1 – 6 (Figure ) were probed in the oxidation of n -hexanoic acid with H 2 O 2 (Table ). The reaction conditions were varied to in order to maximize the selectivity for γ-caprolactone.…”
mentioning
confidence: 90%